Paediatric injury from indoor trampoline centres. Issue 5 (15th August 2016) - Mulligan, Christopher S; Adams, Susan; Brown, Julie
Abstract : Indoor trampoline parks are increasing as a source of injuries among children. We conducted a prospective cohort study, with semi-structured interview and medical record review, of children aged <17 years presenting to a paediatric emergency department following an injury at an indoor trampoline park. In a 6-month period in 2014, 40 such children (55% female) presented to the department. Common mechanisms were individual jumpers falling while attempting a somersault or trick, landing awkwardly on an obstacle such as a ball or protective padding, and multiple users on a single trampoline. Most sustained soft tissue injuries (n=22, 55%) and fractured bones (n=15, 37.5%). One child sustained an unstable cervical fracture/dislocation. Unlike domestic trampolines, where the majority of injuries occur from falling off, most trampoline-park injuries occur on the trampoline surface. These differences require injury prevention strategies that engage children, carers and businesses to meet best practice design and management standards.